Revisiting Dipole-Induced Fluorinated-Anion Decomposition Reaction for Promoting a LiF-Rich Interphase in Lithium-Metal Batteries - Wang, Liu; Guo, Jiahui; Qi, Qi; Li, Xiaotong; Ge, Yuanmeng; Li, Haoyi; Chao, Yunfeng; Du, Jiang; Cui, Xinwei (Nano-Micro Letters, 2025)
Building anion-derived solid electrolyte interphase (SEI) with enriched LiF is considered the most promising strategy to address inferior safety features and poor cyclability of lithium-metal batteries (LMBs). Herein, we discover that, instead of direct electron transfer from surface polar groups to bis(trifluoromethanesulfonyl)imide (TFSI−) for inducing a LiF-rich SEI, the dipole-induced fluorinated-anion decomposition reaction begins with the adsorption of Li ions and is highly dependent on their mobility on the polar surface. To demonstrate this, a single-layer graphdiyne on MXene (sGDY@MXene) heterostructure has been successfully fabricated and integrated into polypropylene separators. It is found that the adsorbed Li ions connect electron-donating sGDY@MXene to TFSI−, facilitating interfacial charge transfer for TFSI− decomposition. However, this does not capture the entire picture. The sGDY@MXene also renders the adsorbed Li ions with high mobility, enabling them to reach optimal reaction sites and expedite their coordination processes with O on O=S=O and F on the broken –CF3−, facilitating bond cleavage. In contrast, immobilized Li ions on the more lithiophilic pristine MXene retard these cleavage processes. Consequently, the decomposition reaction is accelerated on sGDY@MXene. This work highlights the dedicate balance between lithiophilicity and Li-ion mobility in effectively promoting a LiF-rich SEI for the long-term stability of LMBs. Highlights: 1 Single-layer graphdiyne on MXene (sGDY@MXene) heterostructure was fabricated and integrated into polypropylene separators, directing a LiF-rich solid electrolyte interphase and long-term stability of lithium-metal anode. 2 Instead of direct electron transfer from surface polar groups to fluorinated anions, the adsorbed Li ions on sGDY@MXene act as dynamic bridges collaboratively connecting the electron-donating heterostructure to the anion and its derivatives, facilitating interface charge transfer. 3 Dedicate balance between lithiophilicity and high Li-ion mobility is the key to promote the dipole-induced fluorinated-anion decomposition.